Atlas of Human Body Ultrasound Scanning Methods and Diagnostic Applications (Springer Singapore, 2018)
This atlas describes the diagnosis practice and cases of human body ultrasound. It includes anatomic section, standard scan ultrasonogram of every organ, scanning methods and key points, measurement methods, normal value ranges, and clinical significances of every sections. Providing basic information and fundamental principles of ultrasonic diagnosis, it discusses ultrasound scanning of 14 organs in individual chapters. Each section sonography is accompanied by the scanning method, section structure, measuring method and clinical application. The uniform structure and detailed instructions make this atlas an easy-to-use resource for residents to refer to when they encounter specific ultrasound diagnostic problems. Editor Mei Zhang is an associate chief physician and professor at the ultrasonic department, PLA Army General Hospital, Beijing, China.